Political Involvement among Youth in Malaysia: Lessons Learnt - Zalinah Ahmad; Zawiyah Mohd Zain (UIR Press, 2021)
Youth are asset for the country and their ideas may provide significant contribution towards the country development process. They are the driving force towards the progress of the country and their contributions are undeniable in providing new ideas. Other than as the human capitals provided for the workforce, youth are also backbone of the country. Youth involvement in politics happen throughout the world and Malaysia has no exception. Youth have voice out their concern on the government’s policies and actions towards developing process by using available platform such as social media other than joining political parties or any association specifically for youth. The opportunities should be given to this group since country will lose creative, dynamic and innovative ideas from this group, known as Generation Y. The tagline like young leaders have create phenomena to give them opportunities to be leader at every level of government (community, state as well as country). This article will discuss the political involvement based on the survey among students in Universiti Utara Malaysia. Findings showed that internet (social media) has attracted the respondents to know more about politics. Their lower involvement in political parties’ activities are quite contradictory in which their willingness to vote and encourage others to vote during the election process in Malaysia. This paper will highlight the importance of social media as a platform for gaining youth involvement in political scenario in Malaysia.